Künstliche Hüftgelenke, vernetzte Orthopäden und die Entstehung der Medizintechnikindustrie: Zum Gegenstand der Interviews - Ingold, Niklaus; Ochsner, Peter E.; Steinke, Hubert (Maurice E. Müller und die Entwicklung künstlicher Hüftgelenke in der Schweiz. Zeitzeugenbefragungen zur Geschichte einer Medizintechnik, 2023)
In Switzerland, over 20,000 hip joints are replaced with artificial components every year. But how did this routine treatment come about? This article presents Switzerland as an early arena of joint replacement medicine. From 1960 onwards, the orthopaedic surgeons Arnold Huggler, Maurice E. Müller and Bernhard Weber further developed the prosthesis technology of the British surgeon John Charnley. Their efforts made painful hip arthrosis treatable. People who could barely walk regained their mobility. The new medical skills also changed the product ranges of the medical industry partners.